2009
DOI: 10.1111/j.1365-2966.2009.14475.x
|View full text |Cite
|
Sign up to set email alerts
|

3D modelling of the colliding winds in η Carinae - evidence for radiative inhibition

Abstract: The X‐ray emission from the supermassive star η Car is simulated using a 3D model of the wind–wind collision. In the model the intrinsic X‐ray emission is spatially extended and energy dependent. Absorption due to the unshocked stellar winds and the cooled post‐shock material from the primary LBV star is calculated as the intrinsic emission is ray traced along multiple sightlines through the 3D spiral structure of the circumstellar environment. The observable emission is then compared to available X‐ray data, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
207
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(225 citation statements)
references
References 56 publications
(147 reference statements)
18
207
0
Order By: Relevance
“…The X-ray spectrum of η Carinae supports the colliding-wind binary scenario (Usov 1992;Stevens et al 1992;Corcoran 2005;Pittard 2007;Parkin et al 2009). The basic idea is that the LBV emits a rather slow and dense stellar wind (v ∞,1 500 km s −1 , M 1 2.5 × 10 −4 M /yr, Pittard & Corcoran 2002), which collides into the faster, shallower wind originating in the secondary component (v ∞,2 3000 km s −1 ,Ṁ 2 1.0 × 10 −5 M /yr, Pittard & Corcoran 2002).…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…The X-ray spectrum of η Carinae supports the colliding-wind binary scenario (Usov 1992;Stevens et al 1992;Corcoran 2005;Pittard 2007;Parkin et al 2009). The basic idea is that the LBV emits a rather slow and dense stellar wind (v ∞,1 500 km s −1 , M 1 2.5 × 10 −4 M /yr, Pittard & Corcoran 2002), which collides into the faster, shallower wind originating in the secondary component (v ∞,2 3000 km s −1 ,Ṁ 2 1.0 × 10 −5 M /yr, Pittard & Corcoran 2002).…”
Section: Introductionsupporting
confidence: 61%
“…Pittard & Corcoran 2002) and could be affected by many phenomena (Parkin et al 2009). These simulations can reproduce an X-ray luminosity of ≈20 L above a few keV.…”
Section: Energetic Considerationsmentioning
confidence: 99%
“…The wind collision leads to a wind-wind collision cavity (e.g., Pittard & Corcoran 2002;Humphreys et al 2008;Okazaki et al 2008;Parkin et al 2009Parkin et al , 2011Gull et al 2009Gull et al , 2011Madura & Owocki 2010;Madura et al 2012Madura et al , 2013Groh et al 2010Groh et al , 2012a. Radiative transfer models of the wind-wind collision zone were reported by Clementel et al (2015a,b).…”
Section: Introductionmentioning
confidence: 98%
“…Studies of the binary or binary wind-wind collision zone were reported by many authors (e.g., Damineli 1996;Damineli et al 1997Damineli et al , 1998Damineli et al , 2000Damineli et al , 2008bDavidson 1997;Davidson et al 2005Davidson et al , 2015Smith & Gehrz 2000;Smith et al 2004;Smith 2010;Pittard & Corcoran 2002;Corcoran et al 1997Corcoran et al , 2001Corcoran 2005;Ishibashi et al 1999;Soker 2003Soker , 2007Weis et al 2005;Gull et al 2006Gull et al , 2009Gull et al , 2011Gull et al , 2016Nielsen et al 2007;Weigelt et al 2007; Kashi & Soker 2007, 2009aParkin et al 2009;Groh et al 2010Groh et al , 2012bMadura & Owocki 2010;Madura et al 2012Madura et al , 2013Mehner et al 2010aMehner et al , 2011Mehner et al , 2012Mehner et al , 2015Richardson et al 2010;Teodoro et al 2013Teodoro et al , 2016Clementel et al 2015a,b;Hamaguchi et al 2016). The X-ray...…”
Section: Introductionmentioning
confidence: 99%
“…Since the primary star drives a dense, slow (V∼420 km s −1 , Groh et al 2012) wind, the companion must have a very fast wind of ∼3000 km s −1 in order for the WWC to produce the observed hot X-ray plasmas (Pittard & Corcoran 2002). The unseen companion should be, therefore, a massive O star or a WolfRayet star (Verner et al 2005;Parkin et al 2009;Mehner et al 2010).…”
Section: Introductionmentioning
confidence: 99%